Stenotrophomonas maltophilia: Serious Clinical Pathogen - Sanjay Chhibber; Ayaid Khadem Zgair (World Journal of Experimental Biosciences, 2021)
In recent years, the bacterial pathogen Stenotrophomonas maltophilia has emerged as a significant clinical concern, challenging healthcare providers and researchers alike. Once considered an opportunistic pathogen of limited clinical importance, this gram-negative bacterium is increasingly recognized as a formidable adversary, particularly in individuals with compromised immune systems, chronic respiratory conditions, or those undergoing invasive medical procedures. A fundamental aspect of its clinical success lies in its ability to adhere to biotic and abiotic surfaces within the host environment, facilitating colonization and subsequent infection. In this review, we delve into the intricate world of S. maltophilia, exploring its taxonomy, morphology, genetic characteristics, ecological habitat, clinical manifestations, respiratory tract infection, bacterial pneumonia, S. maltophilia and Cystic fibrosis, malignant tumor, and S. maltophilia and Hospital-Acquired Infections (HAI).
Keywords: Immunocompromised patients, Opportunistic pathogen, Respiratory tract, Stenotrophomonas maltophilia.